Requirements and characteristics of websites designed for universities in view of modern digital technologies (Al-Academy, 2024)
The research focuses on evaluating the websites of universities, where five Arabic universities websites were selected using a questionnaire developed and presented to academic experts. The idea of the research emerged to study and develop the requirements for designing universities websites to achieve their privacy, global entry into international rankings, academic and educational goals and societal mission. The research problem was formulated through questions about the characteristics and requirements of websites designed for universities, as well as their criteria and features. The research aims were: (1) Identifying and determining the most important requirements for websites design for universities. (2) Identifying the key features and standards that serve the privacy of websites for universities. (3) Providing insight into the most important design and functional requirements for universities websites. The research community comprised universities websites, while the sample consisted of Arab universities websites, selected to represent a cross-sectional sample of Arab universities. The descriptive analytical approach was adopted to study universities websites based on a questionnaire consisting of twelve questions developed for this purpose and validated by academic experts. The study period for evaluating the websites was 2023, and the results revealed significant variation in the evaluation of the researched universities websites, indicating a need for continuous improvement and development in line with global standards. The research also highlighted the lack of attention to websites design and the extent of their adequacy in meeting the basic requirements for students, researchers and other users, such as information availability, introduction to research centers, laboratories, libraries, service and recreational facilities, student housing and the overall university environment. This is crucial for the university’s recognition amidst international competition, global rankings and sustainable development. The research concluded by presenting an insight into the most important design and functional requirements for universities websites